Potential role of rituximab in metastatic castrate-resistant prostate cancer. (September 2019) - Bindal, Poorva; Jalil, Sharif AA; Holle, Lisa M; Clement, Jessica M
Nearly all men with prostate cancer who are treated with androgen deprivation therapy develop disease progression. There is considerable evidence to suggest that CXCL 13 released by tumor cells leads to B-cell infiltration into the prostate cells. This B-cell infiltration has been postulated to play a role in development of disease progression following androgen-deprivation therapies. We present a case of a patient who achieved remission of metastatic castrate-resistant prostate cancer after receiving rituximab and bendamustine for the treatment of follicular lymphoma. The findings in this report suggest that further investigation is warranted for utilizing B-cell targeted therapy in delaying progression of castrate-resistant prostate cancer.